Future scenarios for teaching mathematical applications in artificial intelligence (robots as a model) at the secondary level in the Kingdom of Saudi Arabia - AboJalbah, Norah Shabeeb; Al-Sulim, Ghalya Hamad (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to present future scenarios for teaching mathematical applications in artificial intelligence (AI) (robots as a model) at the secondary level in the Kingdom of Saudi Arabia. To achieve the study’s objective, the researcher used both the prospective approach through the Delphi and scenarios techniques, and the descriptive approach using content analysis. The study tools consisted of a questionnaire using the Delphi method and a content analysis card. The study population consisted of a group of experts in curricula and teaching methods - educational supervisors, teachers, and specialized faculty members. The study results revealed weaknesses in incorporating mathematical applications in robot programming and dynamics in mathematics, computer science, and information technology curricula at the secondary level. Four scenarios were developed for teaching mathematical applications in AI (AI) (robots as a model) at the secondary level in the Kingdom of Saudi Arabia: (The qualitative shift scenario, the specialized scenario - STEMR academies), which represent optimistic scenarios; (The need-filling scenario), which represents an extension of reality; and (The withdrawal scenario), which represents a pessimistic scenario. In light of the results, the researcher presented a set of recommendations, the most prominent of which were: building foresight laboratories based on the principle of analyzing future trends related to artificial intelligence in the education system, with the participation of society and students in developing appropriate mechanisms and solutions to develop this science in the education system.